2002
DOI: 10.1017/s0003480001001014
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of BRCA1 and BRCA2 in breast and breast/ovarian cancer families shows population substructure in the Iberian peninsula

Abstract: An estimated 5-10 % of all breast and ovarian cancers are due to an inherited predisposition, representing a rather large number of patients. In Spain 1\13-1\14 women will be diagnosed with breast cancer during their lifetime. Two major breast cancer genes, BRCA1 and BRCA2, have been identified. To date, several hundred pathogenic mutations in these two genes have been published or reported to the Breast Cancer Information Core, BIC database (http:\\www.nhgri.nih.gov\ IntramuralIresearchILab transfer\Bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
36
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 8 publications
5
36
0
1
Order By: Relevance
“…In contrast, the evidence that the mutation 330A>G in BRCA1 has lower breast cancer penetrance to age 70 years was very consistent. This variant has been shown to be deleterious, causing aberrant splicing of the transcript that leads to a premature stop codon (42), and represents an estimated 50% of all mutations detected in women from Galicia, in the northwest of Spain (43). Although evidence was marginal (P = 0.09) that breast cancer risks varied between carriers of 330A>G and carriers of all other mutations in BRCA1 (including 185delAG) combined, the estimated cumulative risks of breast cancer to age 70 years were strikingly different, being 27% (95% CI, 0-52%) and 66% (95% CI, 34-83%), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the evidence that the mutation 330A>G in BRCA1 has lower breast cancer penetrance to age 70 years was very consistent. This variant has been shown to be deleterious, causing aberrant splicing of the transcript that leads to a premature stop codon (42), and represents an estimated 50% of all mutations detected in women from Galicia, in the northwest of Spain (43). Although evidence was marginal (P = 0.09) that breast cancer risks varied between carriers of 330A>G and carriers of all other mutations in BRCA1 (including 185delAG) combined, the estimated cumulative risks of breast cancer to age 70 years were strikingly different, being 27% (95% CI, 0-52%) and 66% (95% CI, 34-83%), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The families had been investigated for a number of reasons, including research, directed screening of case series of female or male breast cancer, or attendance at cancer genetic clinics. Some of these families had been included in earlier works [Díez et al, 1999a;Osorio et al, 2000;Campos et al, 2001;de la Hoya et al, 2001de la Hoya et al, , 2002Vega et al, 2002].…”
Section: Subjects and Methods Families And Patientsmentioning
confidence: 99%
“…However, there were some differences due to the geographic origin of the families, with a higher proportion of BRCA1 findings in families from northwest Spain. It has been suggested that the differences found in Galicia [Vega et al, 2002] or Catalonia [Campos et al, 2003], compared with those in other parts of Spain, could be due in part to the presence of founder effects. Alternatively, the lower prevalence of BRCA2 mutations in these families and patients could be due to fewer mutations and to lower penetrance, and/or to later age of onset of BRCA2 breast cancer.…”
Section: Geographic Distributionmentioning
confidence: 99%
“…BRCA1 mutation studies have been reported in different ethnic groups (Panguluri et al, 1999;Ruiz-Flores et al, 2002;Saxena et al, 2002;Zhi et al, 2002;Manguoglu et al, 2003). There have been extensive molecular analyses of the BRCA1 mutations performed in Caucasian populations in countries such as Canada, USA, UK, Sweden, Netherlands, Belgium, Norway, and Spain (Simard et al, 1994;Gayther et al, 1995;Shattuck-Eidens et al, 1995;Johannsson et al, 1996;Peelen et al, 1997;Claes et al, 1999;Borg et al, 1999;Neuhausen., 2000;Osorio et al, 2000;Llort et al, 2002;Vega et al, 2002;de Sanjose et al, 2003;Díez et al, 2003). BRCA1 mutations have been reported in Japanese (Inoue et al, 1995;Matsushima et al, 1995;Katagiri et al, 1996;Miki et al, 1996), Taiwanese (Li et al, 1999), other Asian populations (BIC), and in African Americans (Panguluri et al, 1999).…”
Section: Introductionmentioning
confidence: 99%